2017
DOI: 10.18060/21406
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Muslim Civic Engagement through Faith-Based Community Organizing

Abstract: <p>Muslim Americans often encounter discriminatory practices similar to those experienced by other minority groups living in the U.S. Such practices range from mass incarceration and anti-immigration efforts to racial and religious profiling. In response, a growing number of Muslim American leaders are organizing their communities and collaborating with non-Muslims to address these issues through civic participation and political action. At the same time, several foundations throughout the country have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Because grants and donations are often identified and secured by the organizations’ leaders, organizations with more diverse leadership teams have access to a greater variety of funding sources. For example, faith-based foundations can be a substantial source of funding for these organizations, and an organization with leaders from several different religious traditions likely has ties to a greater variety of faith-based foundations than an organization with leaders from only one religious tradition (Fulton, 2017). Similarly, organizations that are more racially and gender diverse are likely to have access to a greater variety of funding opportunities for which they have a competitive advantage.…”
Section: Resultsmentioning
confidence: 99%
“…Because grants and donations are often identified and secured by the organizations’ leaders, organizations with more diverse leadership teams have access to a greater variety of funding sources. For example, faith-based foundations can be a substantial source of funding for these organizations, and an organization with leaders from several different religious traditions likely has ties to a greater variety of faith-based foundations than an organization with leaders from only one religious tradition (Fulton, 2017). Similarly, organizations that are more racially and gender diverse are likely to have access to a greater variety of funding opportunities for which they have a competitive advantage.…”
Section: Resultsmentioning
confidence: 99%
“…Additional research provides in-depth information on what congregations fund, including social service provision (Ammerman, 2005;Chaves and Tsitsos, 2001;Cnaan, 2002;Fulton, 2016;Scharffs, 2007), community organizing and civic engagement (Wood and Fulton, 2015;Fulton 2017), international missions and aid (Hudson Institute, 2016;Wuthnow, 2009), and religious schools (Greeley et al, 1976;Harris 1996Harris , 1999Ruger, 1999). Targeted studies on religious giving within particular groups or denominations have resulted in data on giving to black Protestant churches (Barnes 2013;Pressley, 1995;Pressley and Collier, 1999), Muslim mosques (Bagby et al, 2001;Bagby, 2012), Orthodox parishes (Krindatch, 2015), Presbyterian congregations (Krohn, 1995;Lunn et al, 2001;Nemeth and Luidens, 1994), Reformed churches , Jewish synagogues (Cohen, 2004;Cohen et al, 2011;Cohen and Landres, 2014), Mormon temples (Curtis et al, 2014(Curtis et al, , 2015Dahl and Ransom, 1999), Baptist churches (Hull et al, 2010), the Evangelical Lutheran Church (Inskeep, 1994;Brewer et al, 2006), and Catholic parishes (Hoge and Augustyn, 1997;Miller et al, 2001Miller et al, , 2002Notarantonio and Quigley, 2009;Rexhausen and Cieslak, 1994;Starks and Smith, n.d.;…”
Section: Available Data and Studies On Congregations' Economic Practicesmentioning
confidence: 99%
“…Beyond the NCS data, other studies reveal how congregations receive revenue from endowments (Hoge and Mead, 1999) and private foundations (Lindsay and Wuthnow, 2010). Additional research provides in-depth information on what congregations fund, including social service provision (Ammerman, 2005; Chaves and Tsitsos, 2001; Cnaan, 2002; Fulton, 2016; Scharffs, 2007), community organizing and civic engagement (Wood and Fulton, 2015; Fulton 2017), international missions and aid (Hudson Institute, 2016; Wuthnow, 2009), and religious schools (Greeley et al, 1976; Harris 1996, 1999; Ruger, 1999). Targeted studies on religious giving within particular groups or denominations have resulted in data on giving to Black churches (Barnes, 2013; Lincoln and Mamiya, [1990] 2003, esp.…”
Section: Available Data and Studies On Congregations’ Economic Practicesmentioning
confidence: 99%
“…Other studies have claimed that funders "leave impact on the table" by avoiding faithbased organizations, doing disservice to their own strategic goals (Eckhart Queenan et al, 2021;Fulton, 2017). Recent studies have shown that faith values and religious communities are still substantial sources of charitable work.…”
Section: Introductionmentioning
confidence: 99%